Examining government officials? perceived risk management and internal control in combating fraud in the public sector - Ilias A.; Baidi N.; Ghani E.K.; Mohammad K.; Omonov A. (Learning Gate, 2025)
This study aims to examine the perception of risk management and internal control in the public sector, specifically concerning preventing fraud. Specifically, this study examines the various aspects of fraud prevention among employees in the public sector, including goal formulation, i nternal environment, and communication of information, risk response, monitoring, risk assessment, and control actions. A total of 537 individuals working in the procurement and finance departments of federal ministries participated in a questionnaire survey conducted using the Committee of Sponsori ng Organizations framework and focused on fraud prevention. This study shows that risk assessment, control actions, and information and communication exert a favorable influence on the prevention of fraudulent activities. This study revealed that risk assessment, control actions, and information and communication exert a favorable influence on the prevention of fraudulent activities. This study can contribute to the government's efforts in improving risk management, addressing corruption, and advancing the Sustainable Development Goal (SDG) 12 and 16 initiatives. ? 2024 by the authors; licensee Learning Gate.